Maritime diplomacy in the 21st century drivers and challenges - Le Mière, Christian (Cass series--naval policy and history, 2014)
[This book] describes and analyses the concept of maritime diplomacy, which has been largely neglected in academic literature. The use of such diplomacy can be interesting not just for the parochial effects of any activity, but because any event can reflect changes in the international order, while acting as an excellent gauge for the existence and severity of international tension. Further, maritime diplomacy can act as a valve through which any tension can be released without resort to conflict. Written in an accessible but authoritative style, this book describes the continued use of coercion outside of war by navies, while also situating it more clearly within the various roles and effects that maritime forces have in peacetime.